Doped stannic oxide nanocrystal capable of being highly dispersed in any water-alcohol ratio and preparation method of doped stannic oxide nanocrystal

By using SnF2 as the tin source and halogen source in the hydrothermal method, oxidizing trimethylamine as the oxidizing agent, combined with organic alkali stabilizer, high-purity in-situ doped tin dioxide nanocrystals that can be highly dispersed in any water-alcohol ratio are prepared, which solves the safety hazards and difficult-to-control particle size in the prior art, and achieves stable dispersion and excellent performance of nanocrystals in different solvents.

CN119569109AActive Publication Date: 2025-03-07ZHEJIANG UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411683021.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The prior art has safety hazards and difficult to accurately control the particle size when preparing tin dioxide nanocrystals, and it is difficult to achieve stable dispersion in different water-alcohol ratio solvents.

Method used

SnF2 and other stannous halides are used as both tin and halogen sources, and trimethylamine is oxidized as an oxidizing agent. High-purity in-situ doped halogen nanocrystals are prepared by a one-step hydrothermal method, and stable dispersion is achieved in any water-alcohol ratio by adding an organic alkali stabilizer.

Benefits of technology

It has achieved high dispersion of tin dioxide nanocrystals in any water-alcohol ratio, with good stability and transparency, and broadened its application prospects in the fields of photoelectricity, catalysis and sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569109A_ABST
    Figure CN119569109A_ABST
Patent Text Reader

Abstract

The invention discloses a doped tin dioxide nanocrystal capable of being highly dispersed in any water-alcohol ratio and a preparation method of the doped tin dioxide nanocrystal. The preparation method comprises the following steps: (1) adding trimethylamine oxide into an aqueous solution containing stannous halide to generate white precipitate, and stirring; (2) carrying out hydrothermal reaction on the mixed solution obtained in the step (1) at 120-200 DEG C for 3-24 hours, carrying out solid-liquid phase separation after the reaction is finished, and dispersing a solid phase in pure water, pure alcohol or a water-alcohol mixed solvent with any water-alcohol ratio to obtain halogen in-situ doped tin dioxide dispersion liquid; and (3) adding an organic alkali stabilizer into the halogen in-situ doped tin dioxide dispersion liquid, and uniformly mixing to obtain the halogen in-situ doped tin dioxide nanocrystal which is highly dispersed in pure water, pure alcohol or a water-alcohol mixed solvent with any water-alcohol ratio. The preparation method is simple, convenient and low in cost, widens the application field of tin dioxide, and has important application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to a doped tin dioxide nanocrystal which can be highly dispersed in any water-alcohol ratio and a preparation method thereof. Background Art

[0002] Tin dioxide (SnO 2 ) is a stable wide bandgap semiconductor with a bandgap of about 3.6eV, which makes it perform well in the optoelectronic field. By doping tin dioxide with elements such as fluorine (F), aluminum (Al), antimony (Sb), indium (In) and titanium (Ti), its electrical, optical and chemical properties can be significantly improved. By doping elements, the band structure of tin dioxide can be regulated, the carrier concentration can be increased and the crystal defect density can be reduced, thereby effectively improving the conductivity, transparency and stability of the material, broadening the application prospects of tin dioxide in electronic and optoelectronic devices, and making it widely used in gas sensors, photocatalysis, transparent conductive films (TCOs), perovskite solar cells (PSCs) and organic light-emitting diode (OLED) devices.

[0003] Compared with other doping elements, SnO 2 ) doped with fluorine (F) has significant performance and economic advantages and is widely used in transparent conductive films, optoelectronic devices, sensors and other fields. At present, the commonly used tin tetrachloride pentahydrate (SnCl 4 ·5H 2 O), stannous chloride (SnCl 2 ) as a tin source, hydrogen fluoride (HF), ammonium fluoride (NH 4 F) as a fluorine source. However, these materials are often accompanied by impurities such as chloride ions, which may reduce the purity of the final product and affect performance and stability. In contrast, stannous fluoride is used as both a tin source and a fluorine source, avoiding the introduction of impurities such as chlorine and ensuring SnO 2 The high purity of single-crystalline SnO is suitable for application fields that require high material purity. 2 nanocubes via ahydrothermal route[J].CrystEngComm,2010,12(2):341-343.) reported a method of (NH 4 ) 2 S 2 O 8 As an oxidant, NaOH as a pH adjuster, stannous fluoride (SnF 2 ) as a tin source, SnO was prepared by hydrothermal method. 2Nanocubes, in this method, (NH 4 ) 2 S 2 O 8 As an acidic salt, it is easy to release protons and accelerate the SnF 2 The hydrolysis of (NH 4 ) 2 S 2 O 8 As an oxidant, soluble Sn(Ⅱ) is oxidized, and the solubility of Sn(Ⅱ) is changed by adding NaOH to adjust the pH value of the solution to prepare SnO with a size of 100-200 nm. 2 Nanocubes. However, due to (NH 4 ) 2 S 2 O 8 It is highly corrosive and irritating and supports combustion, which poses a safety hazard during the experiment. As a strong oxidant, it makes the reaction process difficult to control. 2 The size of nanomaterials is between 100-200nm, and the particle size cannot be precisely controlled.

[0004] When the size of tin dioxide nanocrystals is less than 10nm, they can be called quantum dots. Because their size is close to or smaller than the Bohr radius of electrons or holes, the quantum confinement effect makes them exhibit unique physical and chemical properties. The movement of electrons and holes in quantum dots is confined in three-dimensional space, resulting in discretization of energy levels and enlarged band gaps, so that their light absorption and emission wavelengths can be precisely adjusted by regulating their size. In addition, the energy level structure of quantum dots is similar to the discrete energy levels of atoms or molecules, which significantly enhances their optical properties. Due to the extremely small size of tin dioxide nanocrystals and their high surface energy, quantum dots are easily agglomerated in solutions or solid matrices, resulting in a decrease in their optical and electronic properties. Therefore, ensuring a stable dispersion system of tin dioxide nanocrystals in applications is a prerequisite for achieving their excellent performance.

[0005] At present, SnO 2 ) nanocrystal dispersion system mainly includes pure water phase and pure alcohol solvent. In practical applications, tin dioxide (SnO 2) nanocrystals, the application of pure water phase and pure alcohol solvents is limited by the solvent itself. The application of pure water phase faces the problem of low catalytic reaction rate. At the same time, the fluctuation of pH value and ionic strength of water may lead to the decrease of stability of nanocrystals, thus inducing precipitation or phase separation; pure alcohol solvents have the challenges of insufficient solubility, reduced catalytic selectivity and mismatch between their physicochemical properties (such as polarity) and the requirements of optoelectronic applications in some applications. In contrast, water-alcohol mixed solvents can effectively adjust the polarity of the reaction medium, improve the rate and selectivity of the catalytic reaction, promote the exposure of the active sites of the catalyst, and enhance the catalytic efficiency. In addition, by optimizing the ratio of water and alcohol, the physicochemical properties of the mixed solvent (such as boiling point, viscosity and solvent strength) can be flexibly adjusted to meet the specific needs of different experiments and applications. Therefore, water-alcohol mixed solvents provide a more flexible and efficient environment for the application of tin dioxide nanocrystals, significantly improving their performance in optoelectronics, catalysis and sensors. Summary of the invention

[0006] The present invention provides a doped tin dioxide nanocrystal that can be highly dispersed in any water-to-alcohol ratio and a preparation method thereof. The preparation method of the present invention is a preparation method of halogen-doped tin dioxide nanocrystal in situ, and the size of the halogen-doped tin dioxide nanocrystal in situ can be regulated by adjusting the hydrothermal reaction temperature and reaction time. 2 SnO in situ doped with halogen (e.g., F element) is prepared by using stannous halides as both tin source and halogen source (e.g., fluorine source, etc.) 2 The purity is high; trimethylamine oxide is used as an oxidant with mild oxidizing property, and the oxidation rate of the reaction can be effectively controlled; by adding an organic base stabilizer, the halogen in-situ doped tin dioxide nanocrystals form a stable dispersion in any water-alcohol ratio.

[0007] [1] A method for preparing doped tin dioxide nanocrystals that can be highly dispersed in any water-to-alcohol ratio, comprising the steps of:

[0008] (1) adding trimethylamine oxide to an aqueous solution containing stannous halide to produce a white precipitate, and stirring;

[0009] (2) subjecting the mixed solution obtained in step (1) to a hydrothermal reaction at 120 to 200° C. (e.g., 120° C., 150° C., 180° C., 200° C., etc.) for 3 to 24 hours (e.g., 6 hours, 12 hours, 24 hours, etc.), and after completion of the reaction, separating the solid and liquid phases, dispersing the solid phase in pure water, pure alcohol, or a water-alcohol mixed solvent having any water-to-alcohol ratio, to obtain a halogen in-situ doped tin dioxide dispersion;

[0010] (3) adding an organic base stabilizer to the halogen in-situ doped tin dioxide dispersion, and mixing well to obtain halogen in-situ doped tin dioxide nanocrystals highly dispersed in pure water, pure alcohol, or a water-alcohol mixed solvent with any water-to-alcohol ratio.

[0011] In step (1), the stannous halide may include at least one of stannous fluoride, stannous chloride, stannous bromide and stannous iodide.

[0012] In step (1), the concentration of the stannous halide in the aqueous solution containing the stannous halide may be 7 to 50 g / L.

[0013] In step (1), the molar ratio of the stannous halide to the trimethylamine oxide may be 1:1 to 3.5, and further may be 1:2.5 to 3.5.

[0014] In step (2), the alcohol may include at least one of methanol, ethanol, ethylene glycol, propanol (including any type and amount of various isomers such as n-propanol and isopropanol), and butanol (including any type and amount of various isomers).

[0015] In some embodiments, the water-alcohol mixed solvent of any water-alcohol ratio described in the present invention may refer to a solvent obtained by mixing water and alcohol in any conceivable proportion. Of course, the solvent obtained by mixing water and alcohol in any proportion may also contain any other components of any amount and any type that do not affect the high dispersibility of the halogen in-situ doped tin dioxide nanocrystals.

[0016] In step (2), the concentration of halogen in-situ doped tin dioxide in the halogen in-situ doped tin dioxide dispersion may be 1 to 75 mg / mL, for example, 3 mg / mL, 4 mg / mL, 5 mg / mL, 10 mg / mL, etc.

[0017] In step (3), the organic alkali stabilizer can be added in the form of a liquid (including a solution). Furthermore, the volume ratio of the added organic alkali stabilizer liquid (including an organic alkali stabilizer solution) to the halogen in-situ doped tin dioxide dispersion can be 1:5 to 500. The organic alkali stabilizer liquid (including an organic alkali stabilizer solution) can be directly a commercially available product.

[0018] In step (3), the organic base stabilizer may include at least one of tetrabutylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, ethylenediamine, triethylamine, ethanolamine, and propylamine.

[0019] [2] A halogen in-situ doped tin dioxide nanocrystal that can be highly dispersible in any water-to-alcohol ratio. The halogen in-situ doped tin dioxide nanocrystal that can be highly dispersible in any water-to-alcohol ratio can be prepared by the preparation method described in [1].

[0020] In some embodiments, the halogen in-situ doped tin dioxide nanocrystals that are highly dispersible in any water-to-alcohol ratio are spherical and have an average size of 5 to 14 nm.

[0021] In some embodiments, the arbitrary water-to-alcohol ratio described in the present invention may refer to any situation of anhydrous (i.e., pure alcohol), no alcohol (i.e., pure water), water and alcohol but in an arbitrary ratio (for example, a water-to-alcohol volume ratio of (1:0.2) to (0.2:1), etc., specifically, a water-to-alcohol volume ratio of 1:0.25, 1:0.5, 1:0.6, 1:1, 0.5:1, 0.25:1, 0.2:1, etc.).

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention adopts SnF 2 The size-controlled, high-purity, in-situ halogen-doped SnO2 (SnO) was successfully synthesized by a one-step hydrothermal method using stannous halides as both a tin source and a halogen source (e.g., a fluorine source) and trimethylamine oxide as an oxidant. 2 ) nanocrystals. By adding a small amount of organic base stabilizer, halogen-doped tin dioxide nanocrystals of different concentrations that can be dispersed in any water-to-alcohol ratio are obtained. The steric hindrance effect of the organic base stabilizer and the adsorption of hydroxyl groups to halogen-doped tin dioxide nanocrystals are utilized to effectively solve the dispersion problem in solvents with various water-to-alcohol ratios. The halogen-doped tin dioxide nanocrystals prepared by the present invention are transparent and clear in pure water, pure alcohol, and water-to-alcohol mixed solvents with any water-to-alcohol ratio and have good stability.

[0024] The in-situ doped halogen tin dioxide nanocrystals prepared by the invention have adjustable size and obvious quantum confinement effect, and the preparation method is simple and low in cost, thus broadening the application field of tin dioxide and having important application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The X-ray diffraction diagram of the F in-situ doped tin dioxide nanocrystals prepared in Examples 1 to 3 of the present invention.

[0026] Figure 2 This is a Fourier infrared spectrum of F in-situ doped tin dioxide nanocrystals prepared in Example 1 of the present invention.

[0027] Figure 3 Digital photographs of F in situ doped tin dioxide nanocrystal dispersions without adding an organic base stabilizer in different water-to-alcohol volume ratios prepared using the F in situ doped tin dioxide nanocrystals obtained in step (1) of Example 1 of the present invention (upper figure) and monodisperse size-adjustable F in situ doped tin dioxide nanocrystal dispersions after adding an organic base stabilizer (added concentration of 5 μL / mL dispersion) (lower figure).

[0028] Figure 4 Transmission electron microscope pictures of monodisperse size-adjustable F in-situ doped tin dioxide nanocrystals in a water-alcohol mixed solvent prepared in Examples 1 to 4 of the present invention.

[0029] Figure 5 The particle size distribution diagram of the monodisperse and size-adjustable F in-situ doped tin dioxide nanocrystals prepared in Examples 1 to 4 of the present invention in a water-alcohol mixed solvent.

[0030] Figure 6 This is a transmission electron microscope energy spectrum of the monodisperse size-adjustable F in-situ doped tin dioxide nanocrystals prepared in Example 1 of the present invention in a water-alcohol mixed solvent.

[0031] Figure 7 The UV-visible-near infrared absorption spectra and optical band gap diagrams of monodisperse F in-situ doped tin dioxide nanocrystals in aqueous solution and alcohol solution prepared using the F in-situ doped tin dioxide nanocrystals obtained in step (1) of Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0033] Example 1

[0034] Step (1): 0.235 g of stannous fluoride was weighed and added to 30 mL of deionized water, and stirred for 5 min to prepare a uniform stannous fluoride solution. 0.39 g of trimethylamine oxide was slowly added to the uniform stannous fluoride solution under stirring to produce a white precipitate. After stirring for 15 min, the mixture was added to a 50 mL high-pressure reactor with a polytetrafluoroethylene liner to undergo a hydrothermal reaction. The hydrothermal reaction conditions were: 180° C., 6 h; the reaction product was centrifuged and washed with deionized water and dried to obtain agglomerated F in-situ doped tin dioxide nanocrystals.

[0035] Step (2): dissolving the F in situ doped tin dioxide nanocrystals prepared in step (1) in a mixture of water and ethanol in a volume ratio of 1:0.25 to obtain a tin dioxide-water-alcohol mixed solution dispersion having a F in situ doped tin dioxide concentration of 4 mg / mL, adding a tetrabutylammonium hydroxide solution to the dispersion in an amount of 3 μL / mL of the dispersion, and shaking the mixture evenly to obtain a F in situ doped tin dioxide nanocrystal-water-alcohol mixed solution dispersion.

[0036] Example 2

[0037] Step (1): The only difference from step (1) of Example 1 is that the hydrothermal reaction conditions are changed to: 200°C, 6h, and the rest are the same.

[0038] Step (2): dissolving the F in situ doped tin dioxide nanocrystals prepared in step (1) in a mixture of water and ethanol in a volume ratio of 1:0.5 to obtain a tin dioxide-water-alcohol mixed solution dispersion having a F in situ doped tin dioxide concentration of 3 mg / mL, adding tetraethylammonium hydroxide solution to the dispersion in an amount of 2 μL / mL of the dispersion, and shaking the mixture evenly to obtain a F in situ doped tin dioxide nanocrystal-water-alcohol mixed solution dispersion.

[0039] Example 3

[0040] Step (1): The only difference from step (1) of Example 1 is that the hydrothermal reaction conditions are changed to: 200°C, 12h, and the rest are the same.

[0041] Step (2): dissolving the F in situ doped tin dioxide nanocrystals prepared in step (1) in a mixture of water and methanol in a volume ratio of 1:0.6 to obtain a tin dioxide-water-alcohol mixed solution dispersion having a F in situ doped tin dioxide concentration of 10 mg / mL, adding tetrapropylammonium hydroxide solution to the dispersion in an amount of 4 μL / mL of the dispersion, and shaking evenly to obtain a F in situ doped tin dioxide nanocrystal-water-alcohol mixed solution dispersion.

[0042] Example 4

[0043] Step (1): The only difference from step (1) of Example 1 is that the hydrothermal reaction conditions are changed to: 200°C, 24h, and the rest are the same.

[0044] Step (2): dissolving the F in situ doped tin dioxide nanocrystals prepared in step (1) in a mixture of water and ethanol in a volume ratio of 1:1 to obtain a tin dioxide-water-alcohol mixed solution dispersion having a F in situ doped tin dioxide concentration of 5 mg / mL, adding a tetrapropylammonium hydroxide solution to the dispersion in an amount of 2 μL / mL of the dispersion, and shaking the mixture evenly to obtain a F in situ doped tin dioxide nanocrystal-water-alcohol mixed solution dispersion.

[0045] Example 5

[0046] Step (1): The only difference from step (1) of Example 1 is that the amount of trimethylamine oxide added is changed to 0.35 g, and the hydrothermal reaction conditions are changed to: 150° C., 12 h, and the rest are the same.

[0047] Step (2): dissolving the F in situ doped tin dioxide nanocrystals prepared in step (1) in a mixture of water and methanol in a volume ratio of 0.5:1 to obtain a tin dioxide-water-alcohol mixed solution dispersion having a F in situ doped tin dioxide concentration of 4 mg / mL, adding ethanolamine to the dispersion in an amount of 3 μL / mL of the dispersion, and shaking evenly to obtain a F in situ doped tin dioxide nanocrystal-water-alcohol mixed solution dispersion.

[0048] Example 6

[0049] Step (1): The only difference from step (1) of Example 1 is that the hydrothermal reaction conditions are changed to: 120°C, 6h, and the rest are the same.

[0050] Step (2): dissolving the F in situ doped tin dioxide nanocrystals prepared in step (1) in a mixture of water and isopropanol in a volume ratio of 0.2:1 to obtain a tin dioxide-water-alcohol mixed solution dispersion having a F in situ doped tin dioxide concentration of 5 mg / mL, adding a tetrabutylammonium hydroxide solution to the dispersion in an amount of 7 μL / mL of the dispersion, and shaking the mixture evenly to obtain a F in situ doped tin dioxide nanocrystal-water-alcohol mixed solution dispersion.

[0051] Sample Analysis:

[0052] Figure 1 The X-ray diffraction (XRD) patterns of the in-situ fluorine-doped tin dioxide nanocrystals prepared in Examples 1 to 3 of the present invention are shown in Figure 1. As can be seen from the figure, the intensity of the diffraction peak is relatively high, indicating that the sample has good crystallinity. At the same time, the width of the diffraction peak is relatively large, indicating that the crystal size of the sample is extremely small. By measuring the half-width (FWHM) of the diffraction peak, the Scherrer formula (D = Kλ / βcosθ) is used for calculation, where K is 0.89; λ is 0.15406; β is the half-width of the (110), (101), and (211) crystal planes, and the average grain size of the sample in Example 1 is 6.33nm, and the average grain size of the sample in Example 3 is 6.62nm. Further analysis shows that the three main diffraction peaks in the three embodiments in the figure are all shifted to the right by 0.1° to 0.2° relative to the pure tetragonal tin dioxide crystal structure (PDF#71-0652), and the lattice constant becomes smaller, indicating that in the case of SnF 2 Heteroatoms (F) with a smaller radius than the host atom (O) are in-situ doped into the tin dioxide nanocrystals prepared as the tin source.

[0053] Figure 2 This is the Fourier infrared spectrum of the in-situ fluorine-doped tin dioxide nanocrystals prepared in Example 1 of the present invention. Example 1 at 545 cm -1 The nearby absorption peak is the angular vibration of O-Sn-O, 1640cm -1The absorption peak is the deformation vibration of adsorbed water molecules, 3400cm -1 The absorption peak is the stretching vibration of the OH group.

[0054] Figure 3 The tin dioxide nanocrystal dispersions ( Figure 3 The upper figure in the figure) and the monodisperse and size-adjustable dispersion of doped tin dioxide nanocrystals after adding organic base stabilizer ( Figure 3 It can be seen that the F in-situ doped tin dioxide nanocrystals obtained in step (1) of Example 1 were dispersed in different water-alcohol volume ratios at a concentration of 5 mg / mL. The F in-situ doped tin dioxide nanocrystal dispersion without the addition of an organic base stabilizer was turbid and milky white under natural light, indicating that SnO 2 Agglomeration phenomenon occurred in different water-to-alcohol ratios; the F in-situ doped tin dioxide nanocrystals obtained in step (1) of Example 1 were dispersed in a water-to-alcohol mixed solvent at a concentration of 5 mg / mL. When the volume ratio of water to alcohol in the water-to-alcohol mixed solvent was changed from 1:0 to 0:1, tetrabutylammonium hydroxide was added at a concentration of 5 μL / mL of the dispersion, and the resulting dispersion showed a transparent and stable appearance under natural light, which showed that the SnO 2 The nanocrystals can be fully and evenly dispersed in different water-alcohol ratios, forming a stable transparent colloidal solution.

[0055] Figure 4 The transmission electron microscope photographs of the monodisperse and size-adjustable F in-situ doped tin dioxide nanocrystals in a water-alcohol mixed solvent obtained in Examples 1 to 4 of the present invention. It can be seen that the F-doped tin dioxide nanocrystals are regular spherical, and the addition of an organic base stabilizer makes the fluorine-doped tin dioxide nanocrystals in a monodisperse state, thereby achieving good dispersibility. At the same time, the clearly visible lattice fringes in the sample further prove its high crystallinity. The measurement results show that the interplanar spacings of the tin dioxide nanocrystals on the (110) crystal plane are 0.341nm, 0.338nm, 0.334nm and 0.340nm, respectively, indicating that the in-situ doped fluorine tin dioxide nanocrystal structure is highly ordered and has good crystal quality.

[0056] Figure 5The particle size distribution diagram of the monodisperse and size-adjustable F in-situ doped tin dioxide nanocrystals in a water-alcohol mixed solvent prepared in Examples 1 to 4 of the present invention. It can be seen that the particle size distribution of the F in-situ doped tin dioxide nanocrystals prepared in Examples 1 to 4 is a unimodal distribution with a narrow distribution width, indicating that the grain size is relatively uniform. The average particle sizes of the F in-situ doped tin dioxide nanocrystals prepared in Examples 1 to 4 are 5.76nm, 6.62nm, 8.60nm, and 13.23nm, respectively. It can be seen that by adjusting the temperature and reaction time of the hydrothermal reaction with trimethylamine oxide as the oxidant, the particle size of the nanocrystals can be effectively controlled within a relatively fine range.

[0057] Figure 6 This is a transmission electron microscope energy spectrum of the F in-situ doped tin dioxide nanocrystals dispersed in a water-alcohol mixed solvent prepared in Example 1 of the present invention. It can be seen that the transmission electron microscope energy spectrum shows three elements of tin (Sn), oxygen (O), and fluorine (F), indicating that the tin dioxide nanocrystals prepared with stannous fluoride as the tin source are in-situ doped with fluorine.

[0058] Figure 7 The UV-visible-near infrared absorption spectra and optical band gap diagrams of the aqueous solution and ethanol solution of monodisperse nano-tin dioxide quantum dots prepared by in-situ doping of F with tin dioxide nanocrystals obtained in step (1) of Example 1 of the present invention are shown. The absorbance has a significant absorption peak in the 300-400nm band, and the absorbance slowly decreases in the 400-800nm ​​band, and can still maintain a certain absorption in the entire wavelength range. The optical band gap value is calculated using the formula αhv 2 =A(hv-E g ) is used for calculation, where α is the absorption coefficient, hv is the photon energy, and E g is the optical band gap, common SnO 2 The intrinsic semiconductor band gap is 0-3.6 eV. Due to the doping of fluorine element, quantum confinement effect and increased carrier concentration, the F in-situ doped tin dioxide nanocrystals obtained in step (1) of Example 1 are SnO in aqueous solution. 2 The optical band gap of SnO increases to 4.05 eV in ethanol solution. 2 The optical band gap increases to 4.02 eV.

[0059] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing doped tin dioxide nanocrystals that can be highly dispersed in any water-to-alcohol ratio, characterized in that: Includes steps: (1) adding trimethylamine oxide to an aqueous solution containing stannous halide to produce a white precipitate, and stirring; (2) subjecting the mixed solution obtained in step (1) to a hydrothermal reaction at 120 to 200° C. for 3 to 24 hours, separating the solid and liquid phases after the reaction is completed, and dispersing the solid phase in pure water, pure alcohol, or a water-alcohol mixed solvent with any water-alcohol ratio to obtain a halogen in-situ doped tin dioxide dispersion; (3) adding an organic base stabilizer to the halogen in-situ doped tin dioxide dispersion, and mixing well to obtain halogen in-situ doped tin dioxide nanocrystals highly dispersed in pure water, pure alcohol, or a water-alcohol mixed solvent with any water-to-alcohol ratio.

2. The preparation method according to claim 1, characterized in that: In step (1), the stannous halide includes at least one of stannous fluoride, stannous chloride, stannous bromide and stannous iodide.

3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the stannous halide in the aqueous solution containing the stannous halide is 7 to 50 g / L.

4. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the stannous halide to the trimethylamine oxide is 1:1 to 3.5, and further 1:2.5 to 3.

5.

5. The preparation method according to claim 1, characterized in that: In step (2), the alcohol includes at least one of methanol, ethanol, ethylene glycol, propanol and butanol.

6. The preparation method according to claim 1, characterized in that: In step (2), the concentration of halogen in-situ doped tin dioxide in the halogen in-situ doped tin dioxide dispersion is 1 to 75 mg / mL.

7. The preparation method according to claim 1, characterized in that: In step (3), the organic base stabilizer is added in the form of a liquid, and the volume ratio of the added organic base stabilizer liquid to the halogen in-situ doped tin dioxide dispersion is 1:5-500.

8. The preparation method according to claim 1 or 7, characterized in that: In step (3), the organic base stabilizer includes at least one of tetrabutylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, ethylenediamine, triethylamine, ethanolamine, and propylamine.

9. A halogen in-situ doped tin dioxide nanocrystal that can be highly dispersed in any water-to-alcohol ratio, characterized in that: The halogen in-situ doped tin dioxide nanocrystals that can be highly dispersed in any water-to-alcohol ratio are prepared by the preparation method described in any one of claims 1 to 8.

10. The halogen in-situ doped tin dioxide nanocrystals highly dispersible in any water-to-alcohol ratio according to claim 9, characterized in that: The halogen in-situ doped tin dioxide nanocrystals which can be highly dispersed in any water-alcohol ratio are spherical and have an average size of 5 to 14 nm.

Citation Information

Patent Citations

  • Metal oxide nanoparticles, production method thereof, light-emitting element assembly, and optical material

    CN101070141A

  • A Stannic Oxide Microballoon with Controllable Crystallite Dimension and its Preparation Method and Application

    CN106277040A

  • Preparation method, product and application of heterojunction stannic oxide (SnO2) gas sensitive material

    CN107954468A

  • Alcohol-dispersed anatase titanium dioxide and preparation method and polymer solar cell thereof

    CN109148689A

  • Preparation method and application of tin dioxide nanoparticle organic solvent dispersion liquid

    CN118495580A